Evaluation of Alfalfa (Medicago sativa) and Sericea Lespedeza (Lespedeza cuneata) to Improve Animal Performance in a Tall Fescue-Based Grazing System - Benjamin Tracy; John Fike; Kelsey Brennan; Tianna Blackmon; Sukhmanpreet Kaur (Agronomy, 2022)
Tall fescue [Schedonorus arundinaceous (Schreb.) Dumort. nom. cons. Lolium arundinaceum (Schreb.) Darbysh.] is the dominant pasture grass across much of the southeast of the USA. The species is productive, but grows slowly in summer. Plants also harbor an endophytic fungus (Epichloe coenophiala), which produces alkaloids that are toxic to cattle. Adding summer-productive forages to fescue-based systems may benefit animal production by providing extra herbage and diluting fescue toxins. A three-year study was conducted in Virginia, USA to determine animal and vegetation responses when alfalfa (Medicago sativa) or Sericea lespedeza (Lespedeza cuneata (Dum. Cours.) G. Don) swards were established into tall fescue pastures. Average daily gain (ADG) of steers and seasonal herbage mass dynamics were monitored from 2016 to 2018. Forage and weed species composition measurements were collected to address a secondary objective that sericea might suppress weeds through allelopathy. Steer performance was acceptable (0.73 kg d−1 ADG), but interseeded legumes did not improve weight gain. Steers avoided sericea plants, and this resulted in greater herbage mass accumulation in summer compared with other treatments. Alfalfa was selectively grazed and cover decreased to almost zero by year 3, while sericea cover increased to over 82%. We found little evidence that sericea was allelopathic against weeds. Neither summer-productive legume species proved to be satisfactory in improving summer animal performance in this tall fescue-based grazing system.